2007
DOI: 10.1016/j.biopsych.2007.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Differential Etiology of Posttraumatic Stress Disorder with Conduct Disorder and Major Depression in Male Veterans

Abstract: Background-Epidemiologic studies reveal that posttraumatic stress disorder (PTSD) is highly comorbid with both conduct disorder and major depression in men. The genetic and environmental etiology of this comorbidity has not been examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 47 publications
2
38
0
Order By: Relevance
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 75%
See 2 more Smart Citations
“…Consistent with prior studies of trauma exposure and PTSD, elevated rates of parental problem drinking (Dube et al, 2001;Fergusson et al, 1996b;Sher et al, 1997), MDD (Breslau et al, 1997;Hapke et al, 2006;Kendler et al, 2000;McCutcheon et al, 2009), CD (Afi fi et al, 2009Fu et al, 2007;Kessler et al, 1995;Koenen et al, 2002), regular smoking (Al-Mamun et al, 2007;Breslau et al, 2003;Nelson et al, 2006), and cannabis abuse (Duncan et al, 2008;Kilpatrick et al, 2000;Nelson et al, 2006;Reed et al, 2007) were observed in women who had experienced traumatic events-both those who developed PTSD and those who did not-compared with women who did not report any trauma exposure. Much of the prior research in this area has involved comparing rates of co-occurring psychopathology and psychosocial risk factors in individuals with PTSD with those who do not meet diagnostic criteria, without regard to the trauma exposure status of individuals in the non-PTSD group or, conversely, comparing traumaexposed with non-trauma-exposed individuals, without regard to the PTSD status of individuals in the traumaexposed group.…”
Section: Association Of Posttraumatic Stress Disorder and Trauma Withsupporting
confidence: 75%
“…Kessler et al (1997) found that nearly half (48.5%) of women with alcohol dependence (AD) met MDD criteria. The strong association between PTSD and CD is also well documented (Fu et al, 2007;Koenen et al, 2002Koenen et al, , 2005. According to National Comorbidity Survey data (Kessler et al, 1995), the prevalence of CD in individuals meeting diagnostic criteria for PTSD is nearly triple that of those without a PTSD diagnosis (15.4% vs. 5.9%).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…A large proportion of the genetic liability for PTSD is also shared with other mental disorders such as anxiety and panic disorder (Goenjian et al, 2008), major depressive disorder (MDD) (Fu et al, 2007;Sartor et al, 2012), and substance use (Xian et al, 2000), hence genes that confer risk for PTSD may also influence risk for other psychiatric disorders and vice versa (Nugent et al, 2008). Such pleiotropic effects have been demonstrated across several psychiatric disorders (Solovieff et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, genetic influences on major depression account for the majority of the genetic variance in PTSD. Genetic influences common to major depression account for the majority of the genetic variation in PTSD [47,72]. Genetic influences common to generalized anxiety disorder and panic disorder symptoms account for approximately 60% of the genetic variance in PTSD [20] and those common to alcohol and drug dependence [139] and nicotine dependence [74] account for over 40%.…”
Section: Ptsd Is Heritablementioning
confidence: 99%